2013
DOI: 10.1016/j.parkreldis.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of specific executive functions in mobility in Parkinson's disease

Abstract: a b s t r a c tPostural instability and gait disorders (PIGD) in Parkinson's disease (PD) seem to be associated with executive dysfunction. We investigated which specific executive functions are associated with functional mobility in mildly affected PD patients. Functional mobility (Timed Up&Go Test, TUG), PIGD score, (spatial) working memory, set shifting, response inhibition and response generation were assessed in a large cohort of 232 non-demented PD patients. Both performance on the TUG and PIGD score wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
(15 reference statements)
7
26
0
2
Order By: Relevance
“…Better cognitive functions were seen more in patients with severe akinesia, in comparison to patients with severe tremor. Our results extend prior studies showing relationships between motor and cognitive measures in PD (Riggeal et al, 2007; Colman et al, 2009; Wylie et al, 2012; Smulders et al, 2013), and further show that the effects of MAO-I on neuropsychological, affective, and quality of life measures in PD depends on the subtypes of PD.…”
Section: Discussionsupporting
confidence: 91%
“…Better cognitive functions were seen more in patients with severe akinesia, in comparison to patients with severe tremor. Our results extend prior studies showing relationships between motor and cognitive measures in PD (Riggeal et al, 2007; Colman et al, 2009; Wylie et al, 2012; Smulders et al, 2013), and further show that the effects of MAO-I on neuropsychological, affective, and quality of life measures in PD depends on the subtypes of PD.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have classified newly diagnosed/ untreated PD patients, or relatively mildly affected [32] into subtypes demonstrating heterogeneity in early PD [2,29,36]. This may work for ''early patients'', however, our findings indicate that categorization may be distorted in the more advanced stages of the disease.…”
Section: Considerations In Regards To Classification Into Pigd and Tdmentioning
confidence: 62%
“…Various forms of classification have been described in the literature [2,3,[28][29][30][31][32]. Clinical separation into PIGD and TD types has been the most extensively studied classification method [33,34].…”
Section: Considerations In Regards To Classification Into Pigd and Tdmentioning
confidence: 99%
“…These results contrast with previous research demonstrating associations between working memory and gait performance in people with PD. 36 This difference may be a reflection of the medication state of the participants tested. Previous research has shown that working memory deficits are improved with dopaminergic medication.…”
Section: Cognitive and Gait Performance In Parkinson Diseasementioning
confidence: 99%